Correlational Study Between Temporal Processing and Reading in School Children - V´ásquez Arango, Claudia Fernanda; Muñetón Ayala, Mercedes Amparo (Cuadernos de Lingüística Hispánica, 2023)
The ability to perceive temporal information in short periods is referred to as temporal processing (TP). This study aims to analyze the relationship between temporal processing and reading at an evolutionary level, throughout the cycle of primary grades 1-5. The participants were 470 boys and girls (5-13 years old). They were evaluated in 4 temporal order judgment tasks (OJT) –2 of linguistic and nonlinguistic auditory temporal processing and 2 of linguistic and non-linguistic visual temporal processing– and in reading tasks. Among the results, significant correlations were found between the general temporal processing tasks and the reading tasks, proportional to school grade, and between the temporal order judgment tasks and the majority of the reading tasks in 1st, 4th, and 5th grade. The above suggests a correspondence between the evolutionary development of temporal processing and that of reading. On the other hand, this development could be more sensitive to the beginning and end of basic education.